(untitled) (Journal of Philosophy Culture and Political Science, 2023)
The multidimensionality of the phenomenon of craft and aspects of its study raises theoretical and methodological questions, which have horizons of their own subject matter and are linked to a specific scientific interest, and find their research field in this article. The aim of the paper is to try to make sense of craft in the focus of the discourse of postclassical philosophy and culture, actualising questions of the being of this phenomenon. This is due to the fact that craft in modern culture has been on the periphery of intellectual reflection, although there is a growing practical interest in it worldwide and in Kazakhstan in particular. Crafts are mostly studied objectively within the framework of ethnographic, culturological and art history studies in pragmatic, aesthetic, semiotic and artistic aspects. However, the issues of ontological nature of this phenomenon and the definition of its essential foundations have not received their proper explication in the methodology of socio-humanitarian sphere. The analysis of craftsmanship undertaken in this article has shown a limited understanding and interpretation of the meaning of its definition expressed in the term “manual production”. This, in turn, prevents the full disclosure of the meanings and cultural meanings of craft and the assumption of variability in its understanding. The analysis of the key concepts of structural anthropology by C. Lévi-Strauss and ontological phenomenology by M. Heidegger helped to reveal the “human” content of the value of craft, its ontological significance as a cultural phenomenon that preserves the memory of “handiness” - the expression of direct sensuality to the surrounding world as being. The results of the study can be useful as a theoretical and methodological material in the practice of cultural, scientific, educational communities which have shown interest in the phenomenon of crafts as intangible cultural heritage. The analytical part of the work, which contains the experience of philosophical and cultural comprehension of the phenomenon of crafts, may be interesting for the researchers of the ontology of culture and its elements. The research was implemented within the project AR09259862 “Research of traditional crafts of modern Kazakhstan: the status and search for ways of preservation” by the Ministry of Science and Higher Education of the Republic of Kazakhstan. Key words: craft, handiness, item, product, value